The Inﬂuence of Teachers' Roles and Parental Communication on Children's Self- Protection Behaviors in Eﬀrots to Prevent Sexual Violence at MI Nurul Islam - Ainayah Alfatihah Al azmi Azmi; Mappanyompa; Madiyah Hayati (Literasi: Jurnal Ilmu Pendidikan, 2026)
This study was prompted by the rising number of cases of sexual violence against children in Indonesia. Data from Simfoni PPA through June 2025 recorded 13,845 reported cases of violence against women and children, with sexual violence being the most prevalent form of violence. Additionally, KPAI recorded 2,031 cases of child rights violations involving 2,063 child victims, while FSGI reported 101 victims of sexual violence in educational settings during 2024. These conditions highlight the importance of strengthening self-protection behaviors among elementary school-aged children as a means to reduce the risk of sexual violence within the family, school, and community. This study aims to analyze the influence of teachers’ roles and parental communication on self-protection behaviors among elementary school-aged children. This study employed a quantitative method using a survey approach involving 43 fifth-grade students at MI Nurul Islam Sekarbela through saturation sampling. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability, and were subsequently analyzed using multiple linear regression after meeting the classical assumption tests. The results of the study indicate that the teacher’s role has a significant effect on self-protection behavior (p=0.008), whereas parental communication does not have a significant partial effect (p=0.115). Taken together, these two variables account for 30.0% of the variance in self-protection behavior. Based on the results of this study, strengthening the role of teachers is important in supporting children’s self-protection behaviors, while improving the quality of parental communication remains necessary to strengthen the synergy between school and family. This study is expected to serve as a foundation for the development of child protection programs through the creation of educational modules, teacher training, and the strengthening of communication between parents and children to foster self-protection behaviors starting in elementary school.